Targeting cancer metabolism: dietary and pharmacological interventions - Vernieri, Claudio (Cancer Discov, 2016)
Most tumors display oncogene-driven reprogramming of several metabolic pathways, which are crucial to sustain their growth and proliferation. In recent years, both dietary and pharmacological approaches that target deregulated tumor metabolism are beginning to be considered for clinical applications. Dietary interventions exploit the ability of nutrient-restricted conditions to exert broad biological effects, protecting normal cells, organs and systems, while sensitizing a wide variety of cancer cells to cytotoxic therapies. On the other hand, drugs targeting enzymes or metabolites of crucial metabolic pathways can be highly specific and effective, but must be matched with a responsive tumor, which might rapidly adapt. In this Review, we illustrate how dietary and pharmacological therapies differ in their effect on tumor growth, proliferation and metabolism, and discuss the available preclinical and clinical evidence in favor or against each of them. We also indicate, when appropriate, how to optimize future investigations on metabolic therapies on the basis of tumor- and patient-related characteristics.